GARANTIZAR EL PRINCIPIO DE PROGRESIVIDAD CONSTITUCIONAL EN EL IMPUESTO AL VALOR AGREGADO - Torres Sánchez, Karina Michelle (2021)
This thesis entitled: "Guarantee the Principle of Constitutional Progressivity in Value Added Tax", constitutes the final report of the entire investigation process carried out, and whose main foundation refers to the obligation of the State to guarantee compliance with the objectives of the Development Regime as stated in the Constitution of the Republic of Ecuador, specifically the redistribution of wealth through tax policy, and thereby also guarantee constitutional principles such as tax progressivity and collection sufficiency, principles that are also included in Article 300 of the Constitution of the Republic of Ecuador where it is emphasized that the tax policy will promote redistribution and stimulate employment; and that direct and progressive taxes should be prioritized. All this denotes that in our country there is an economic and tax policy recognized at the constitutional level that seeks to achieve tax justice that reduces the inequality gaps that always affect the most vulnerable groups. The creation of tax legislation with redistributive characteristics responds to a sense of co-responsibility and distribution of the tax burden in a balanced way, in such a way that the principle of progressivity and collective solidarity is met. The present study shows that the Value Added Tax by its nature is a tax that taxes consumption regressively, that is, it does not observe the taxable capacity of a person, but that by reason of the principle of generality everyone must assume the payment of this Consequently, it affects those who have less income, and since the Value Added Tax is one of the taxes that generates the highest collection for the State, it is necessary to reform its structure in such a way that the regressivity of this tax is mitigated, and achieve efficient tax collection; being one of the most accepted theories the differentiation of tariffs in an objective way. - 5 - This research work contains conceptual references, doctrinal and legal elements that allow the understanding of the legal problem raised; Likewise, through the application of different methods and techniques, all the general and specific objectives were met; and specifically, through the application of surveys and interviews, the acceptance by Legal Professionals for the reform approach was obtained. Finally, the result of the entire investigation process evidenced the viability and acceptance of formulating as a legal proposal a tax reform to Article 65 of the Internal Tax Regime Law.